Needs Analysis of Psychosocial Module Development Based on Psychoeducation Approach for Public University Students in Malaysia - Salleh Amat; Harizah Izyan Samsudin; Abu Yazid Abu Bakar; Mohd Izwan Mahmud; Mohd Hasrul Kamarulzaman (MDPI AG, 2021)
This study is a needs analysis that aims to develop a psychosocial module based on a psychoeducation approach in order to strengthen the assertiveness, social skills, and psychological well-being of public university students in Malaysia. The specific objectives of this study were to identify the perceptions of university students on the need to design and build a psychosocial module, identify the constructs that should be included in the phase of designing and building of the psychosocial module as well as the support that has been received and the support that the students desire while on campus. This survey study utilized a questionnaire distributed to a total of 286 first year students studying at three public universities in Malaysia. The data obtained were analyzed by using descriptive statistics. The findings of the study showed a highly positive response from the students toward the development of a psychosocial module and the constructs listed in the questionnaire. Implications from this study can further solidify the constructs that should be included in the design and construction of the psychosocial module as well as identify the availability of the approaches, strategies, and support activities that have been received and desired by the students.